Decreased Reoperations and Improved Outcomes With Reverse Total Shoulder Arthroplasty in Comparison to Hemiarthroplasty for Geriatric Proximal Humerus Fractures: A Systematic Review and Meta-Analysis. Issue 1 (January 2019) - Austin, Daniel C.; Torchia, Michael T.; Cozzolino, Niki H.; Jacobowitz, Lauren E.; Bell, John-Erik
Abstract : Objectives: We sought to compare range of motion, clinical outcome scores, and complications after reverse total shoulder arthroplasty (RSA) and hemiarthroplasty (HA) in geriatric patients with acute proximal humerus fractures. Data Sources: We searched MEDLINE (1946–2017), EMBASE (1947–2017), the Cochrane Central Register of Controlled Trials (1898–2017) andClinicalTrials.gov in October 2017. No limits were used in the database search. We also manually reviewed reference lists of included studies. We did not restrict studies based on language. Study Selection: We included all randomized controlled trials and cohort studies in which the study population had a mean age of 65 years or older, received RSA or HA to treat an acute proximal humerus fracture, and had a minimum follow-up of 6 months. Data Extraction: Two independent reviewers used a standardized data collection form to extract relevant information from included studies. Discrepancies were resolved by a consensus or a third party if consensus could not be reached. Study authors were contacted for missing or incomplete data. Data Synthesis: Using a random effects model, we calculated mean differences (MD) and standardized mean differences (SMD) for continuous outcomes; we calculated relative risk for dichotomous outcomes. Results: Fifteen studies were included in the meta-analysis, including 421 patients treated with RSA and 492 treated with HA for a total of 913 patients. Compared with HA, the RSA group had significantly improved pain scores (SMD = 0.74, P < 0.001), outcome scores (SMD = 0.63, P < 0.001), and forward flexion (MD = 24.3 degrees, P < 0.001). Compared with RSA, the HA group had a significantly increased risk of reoperation (relative risk = 2.8, P = 0.02). There were no differences between the groups with regard to external rotation ( P = 0.31) or deep infection ( P = 0.90). Conclusions: Aggregating available research suggests that RSA results in improved range of motion, clinical outcome scores, and rates of all-cause reoperation with no difference in infection rates. Using RSA for the treatment of acute proximal humerus fractures in the elderly population may result in improved short- and medium-term outcomes compared with HA. Future work should evaluate long-term outcomes to see if the benefits of RSA persist. Level of Evidence: Therapeutic Level III. See Instructions for Authors for a complete description of levels of evidence. Abstract : Supplemental Digital Content is Available in the Text.